Bamboo leaf extract ameliorates diabetic nephropathy through activating the AKT signaling pathway in rats - Ying, Changjiang; Mao, Yizhen; Chen, Lei; Wang, Shanshan; Ling, Hongwei; Li, Wei; Zhou, Xiaoyan (International journal of biological macromolecules, 2017)
Diabetic nephropathy (DN) is one of the most severe diabetic complication and it is becoming become a worldwide epidemic, accounting for approximately one-third of all case of end-stage renal disease. However, the underlying mechanism and strategy to alleviate renal injury remain unclear. In the present study, we assessed the protective effect of bamboo leaf extract on the DN, and investigated the underlying mechanism by which bamboo leaf extract ameliorating DN. Diabetic rats were induced by 4 weeks high sugar and high fat diet, and then injected a single dose of STZ (35mg/kg) into abdominal cavity. Different dose of bamboo extract (50mg/kg, 100mg/kg and 200mg/kg) were orally administered every day for a period of 12 weeks. Body weight, blood glucose, glycosylated hemoglobin A1c (HbAlc), blood urea nitrogen (BUN), serum creatinine (Scr), and 24-hour urinary protein (24 h-UP) were assessed. Total superoxide dismutase (T-SOD) activity and MDA (methane dicarboxylic aldehyde, MDA) level were tested by assay kit. Microstructural changes were observed by hematoxylin–eosin (HE) staining and electron microscopy. Expression of phosphorylated ser/thr protein kinase (P-AKT), phosphorylated glycogen synthase kinase-3 beta (P-GSK-3β), B cell lymphoma/leukemia 2-associated X protein (BAX) and cleaved-cysteinyl aspartate-specific proteinase-3 (Cleaved Caspase-3) were measured by Western-Blotting (WB). Results showed that diabetic rats had weight loss, high blood glucose, HbAlc, BUN, Scr and 24-UP and T-SOD activity were increased and MDA level was decreased in diabetic rats. Moreover, hyperglycemia could injury renal tissue ultrastructure, inhibit P-AKT level and increase P-GSK-3β, BAX and Cleaved Caspase-3 levels in rats. However, bamboo leaf extract treatment could reduce body weight loss, BUN, Scr, 24 h-UP and MDA level, improve T-SOD activity and alleviate renal injury in diabetic rats. Furthermore, bamboo leaf extract increased P-AKT level, decreased P-GSK-3β, BAX and Cleaved Caspase-3 levels in STZ-diabetic rats. In conclusion, our study suggested that bamboo leaf extract ameliorated DN in diabetic rats, and this protective effect is possibly related to suppressing oxidative stress through activating AKT signaling pathway. Bamboo leaf extract treatment may be a potential promising therapy for DN.